2021
DOI: 10.3390/polym13111713
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sulfonated Poly(Arylene Ether Sulfone)s Containing Aliphatic Moieties for Effective Membrane Electrode Assembly Fabrication by Low-Temperature Decal Transfer Methods

Abstract: The purpose of this study was to investigate the effect of the aliphatic moiety in the sulfonated poly(arylene ether sulfone) (SPAES) backbone. A new monomer (4,4’-dihydroxy-1,6-diphenoxyhexane) was synthesized and polymerized with other monomers to obtain partially alkylated SPAESs. According to differential scanning calorimetry analysis, the glass transition temperature (Tg) of these polymers ranged from 85 to 90 °C, which is 100 °C lower than that of the fully aromatic SPAES. Due to the low Tg values obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This result is significant when applying the decal transfer method and analyzing the resistances within the MEAs. The decal transfer method with HC-PEMs requires a much higher temperature and/or pressure than the PFSA-based PEM due to its high glass-transition temperature (PFSA ∼ 120 °C and HC > 200 °C), high rigidity, and low compatibility with CL containing a PFSA ionomer. Therefore, performing the decal transfer method at low pressure and temperature by employing enhanced interfacial bonding properties can achieve advantages in the MEA manufacturing process and high-performance PEMFC with low-cost HC-PEMs.…”
Section: Resultsmentioning
confidence: 99%
“…This result is significant when applying the decal transfer method and analyzing the resistances within the MEAs. The decal transfer method with HC-PEMs requires a much higher temperature and/or pressure than the PFSA-based PEM due to its high glass-transition temperature (PFSA ∼ 120 °C and HC > 200 °C), high rigidity, and low compatibility with CL containing a PFSA ionomer. Therefore, performing the decal transfer method at low pressure and temperature by employing enhanced interfacial bonding properties can achieve advantages in the MEA manufacturing process and high-performance PEMFC with low-cost HC-PEMs.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a blind test data set for other advanced PEMs was also collected after the predictive model had been constructed. It contains 33 polarization curves, retrieved from six original literature studies reported in the recent year till July 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Among these, most consideration relates to the PEMFC and AFC because of their operating temperature, which can correspond to the room temperature [ 41 , 42 ]. Moreover, hydrogen was applied to PEMFC and AFC as fuel in the anode side, and the reaction happened without any other harmful gases and byproducts [ 43 ]. The operating principle and reaction process of PEMFC and AFC has been schematically illustrated in Figure 1 a and Figure 1 b, respectively [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%